Gestión operativa y su incidencia en el centro de emprendimiento de la prefectura de Los Ríos en el Cantón Babahoyo, año 2023 - Jiménez Terán, Carlos Alfredo (2024)
Efficient operational management maximizes productivity, minimizes costs and ensures quality, essential for sustainable business success. The general objective was “to analyze operational management and its impact on the Entrepreneurship Center of the Prefecture of Los Ríos in the Babahoyo canton in the year 2023.” The study used a descriptive approach to analyze processes and perceptions, and an exploratory approach to identify underlying causes and propose improvements, collecting data through interviews, surveys and direct observations. Deductive, inductive, descriptive and analytical methods were applied. The sample was made up of 70 entrepreneurs. While the interview was conducted with two directors. The results show that the Babahoyo Entrepreneurship Center, according to the interview, highlights the priority given to entrepreneur satisfaction and effective communication, but needs to improve the use of resources and periodic evaluations, requiring strategic measures to guarantee operational efficiency, such as the implementation of regular evaluations with indicators for optimal management. For their part, entrepreneurs perceive the center's support positively, but areas for improvement are identified, such as training in financing and business skills. The analysis of indicators shows effective management, with high satisfaction and fulfillment of goals, although the response to requests and the success rate of ventures must be improved. In conclusion, the results validate the positive impact of the center on local economic development, with strategies that can be implemented by applying the designed indicators permanently.